2016
DOI: 10.14254/1800-5845.2016/12-2/11
|View full text |Cite
|
Sign up to set email alerts
|

The Size of Innovation Space as a Factor of Innovation Activity in Regions

Abstract: The research objective is to obtain and ground the quantitative characteristics of the impact of science and business on the results of innovation activity of the Russian Federation subjects. Under such results the number of patents issued and new production technologies developed are considered. Hypotheses testing is conducted enabling to establish the relationship between the innovation activity of a region and the number of potential links between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…3, allows you to rank the regions in terms of efficiency level. In the works of the authors (Aivazyan et al, 2016, Aivazyan, Afanasyev, 2015, 2016 it was shown that the specification of model (1) and residual distribution functions can have a significant effect on the values of technical efficiency estimates. In this case, the ranks of these estimates have the property of resistance to the specification of the mode.…”
Section: Problems Of Comparison Of Innovative Activity Of Regions Difmentioning
confidence: 99%
“…3, allows you to rank the regions in terms of efficiency level. In the works of the authors (Aivazyan et al, 2016, Aivazyan, Afanasyev, 2015, 2016 it was shown that the specification of model (1) and residual distribution functions can have a significant effect on the values of technical efficiency estimates. In this case, the ranks of these estimates have the property of resistance to the specification of the mode.…”
Section: Problems Of Comparison Of Innovative Activity Of Regions Difmentioning
confidence: 99%